Discovery of potent cox-2 binding triazolo/tetrazoloquinazoline derivatives as novel venotonic candidates: molecular docking and structure-activity relationships - Antypenko, L.; Shabelnyk, K. P.; Antypenko, O. M.; Zarutska, M.; Maletsky, M. M.; Шабельник, Костянтин Петрович; Антипенко, Олексій Миколайович; Малецький, Микола Миколайович (My University, 2025)
Chronic venous insufficiency (CVI) is a progressive pathological condition characterized by inadequate venous return of blood from the lower extremities. The pathophysiology involves venous hypertension, valvular insufficiency, and subsequent activation of an inflammatory cascade, leading to endothelial dysfunction, increased capillary permeability, and tissue hypoxia. Current therapeutic approaches remain limited, as existing venotonics demonstrate modest efficacy and require long-term use to achieve sustained clinical benefits. This study investigates novel triazolo/tetrazoloquinazoline derivatives as potential venotonic drug candidates using molecular docking assays against one of the key inflammatory targets implicated in the pathophysiology of CVI. Our computational approach reveals promising binding profiles for several compounds, particularly against cyclooxygenase-2 (COX-2), with binding affinities superior to or comparable to established reference compounds. These results provide a basis for further pharmacological and toxicological evaluations aimed at developing more effective and targeted therapies.